Comparative Analysis of Disabled Accessibility Needs of Heritage Building in Perak - Zahari, Nurul Fadzila; Harun, Saidatul Farhana; Ahmad, Nur Azfahani; Ahmad Zawawi, Zuraihana; Aras Agus Salim, Nuzaihan (EDP Sciences, 2016)
Tourism sector was the sixth highest national income provider to the Malaysian economy in 2014. In order to replenish Malaysian economy through tourism, the Malaysian government has to diversify the present tourism products and offers a wide variety of tourism packages. This has mentioned in the National Key Results Area (NKRA) development platform highlighted in the 10th Malaysian Plan. Therefore, the tourism sector needs to continuously re-engineer and adapt its business model to suit every customer’s needs and demands, including disabled people. At the moment, one of the highest tourist attraction contributors in Malaysia is the heritage building sector. The heritage building sector in Malaysia becomes popular due to its diverse historical background and culture. It attracts local and international tourists to visit. However, the lack of facilities provided especially for the disable people has hindered its future prospects to become globally popular. The national heritage should be viewed, explored and enjoyed by everybody without discriminating anyone. Insufficient of provision for disable facilities in heritage act has caused barrier to the disable people to enjoy and visit the heritage sites. The objective of this research is to analyze the comparative data that been retrieved in the field of selected case study. It will be carried out by visiting the selected case study, observation and documentary analysis. This research aims to do a comparative analysis of Disabled Accessibility needs of Heritage Building in Perak. The findings of this research will alert the needs of disabled in visiting the heritage building and documented for future research.